The impact of conservation tillage on soil quality and potential for climate change mitigation - Mangalassery, Shamsudheen (2013)
Conservation tillage is generally considered as an important component of sustainable agriculture. The benefits of conservation tillage have been presented as reducing runoff, enhancing water retention and preventing soil erosion. There is also general agreement that it can be used to conserve and enhance soil organic carbon levels to some extent. However, its applicability in mitigating climate change has been extensively debated, especially when the whole profile of carbon in soil is considered along with a reported risk of enhanced N2O emissions under conservation tillage. The suitability of conservation tillage in mitigating climate change and enhancing carbon sequestration is addressed in this research in an integrated approach combining characterisation of the soil porous architecture and other chemical and biological properties. Novel analytical tools such as X-ray Computed Tomography were used to characterise the 3-D soil pore network under conservation tillage for the first time. The study indicated zero tilled soils had a lower net emission of greenhouse gases on a CO2 equivalent basis indicating potentially zero tillage can be used to mitigate climate change. The net global warming potential under conventional tillage was 20% higher than zero tilled soil. A model developed to predict the greenhouse gas emissions from soil found that soil pore characteristics such as porosity played a significant role in the emission of greenhouse gases such as CO2 and CH4 among other factors such as microbial biomass carbon, bulk density and shear strength. Soil porosity alone accounted for 39.7% of the total variation for CO2 flux which was larger than any other parameter including microbial biomass carbon and soil carbon. Soil pore characteristics were revealed as one of the important determinant in aiding the GHG flux in soil. However N2O emission from soil was mainly dependent on soil moisture, microbial biomass carbon and microbial biomass nitrogen. It was also found that zero tilled soils contained 9% more soil carbon and 30% higher microbial biomass carbon than the tilled soil. It was found that tillage mediated aggregate changes could bring changes in carbon storage in soil depending on texture of soil. Increased microbial activity was evident at zero tilled soils as observed from the increased activities of hydrolysing and oxidising enzymes. The preservation of aromatic structures during residue decomposition might have contributed to enhanced sequestration of carbon under zero tilled soils as revealed by the FTIR data. The study indicates that soil management practices strongly influence other properties and by making a suitable choice of the tillage system, a comparative reduction in greenhouse gas emissions could be achieved at the same time enhancing sequestration of carbon.